Essential University Physics: Volume 1 (4th Edition)

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 4 - Section 4.6 - Newton’s Third Law - Example - Page 66: 4.4


$F_{21} = -F_{12} = \frac{m_1}{m_1+m_2}F$

Work Step by Step

We start with the equation for acceleration, and then we simplify: $a = \frac{F}{m} \\ a = \frac{F}{m_1+m_2} $ We know that $F_{12} = m_2a$, so it follows: $F_{12} = \frac{m_2}{m_1+m_2}F$ Thus: $F_{21} = -F_{12} = \frac{m_1}{m_1+m_2}F$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.